Temperament of Psittaciformes: A systematic review - de Almeida, Gustavo Nunes; Ramos, Gabriela; de Jesus, Larissa Gomes; Branco, Maria Eduarda Caçador; de Azevedo, Cristiano Schetini; Sant'Anna, Aline Cristina [UNESP] (Elsevier, 2024)
The study of temperament of the order Psittaciformes has been expanding over the past decades due to the publication of papers investigating individual differences in various species. This review aimed to integrate studies on the temperament of Psittaciformes in a systematized manner, focusing on methodological aspects. It also aimed to reveal the main dimensions of temperament described for these species, identify possible gaps and suggest new themes that deserve the scientific community's attention. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was followed, and the search was conducted using Population, Intervention, and Context (PICo) terms. Three databases were used (Scopus, Web of Science, and CABI), resulting in a total of 24 publications included. The most used term to express consistent interindividual behavioral differences was ‘personality’ (11; 45.83 %), followed by ‘temperament’ (8; 33.33 %), without a clear distinction of both in this research field. Studies on temperament were conducted within the families Psittacidae (18; 75 %), Psittaculidae (4; 16.67 %) and Cacatuidae (2; 8.33 %), with the genus Amazona being the most investigated (14; 58.33 %). Regarding context, all papers used animals under human care (kept in captive environments). In total, 22 temperament dimensions were compiled, with ‘boldness’ (or ‘shy-bold’ axis or ‘shyness-boldness’), ‘neophobia/neophilia’, ‘exploration’, and ‘vigilance’ being the most common. Quantitative methods of assessment (coding) were more commonly applied, being used in 19 (79.17 %) publications, compared to qualitative ones (rating methods). Among the factors related to temperament, pre- and post-release behavior was the most investigated (5; 20.83 %). We could conclude that studies were concentrated on a few taxonomic groups, highlighting the need to broaden the subjects studied, including other families, genera, and species. Furthermore, it would be interesting to expand the temperament evaluations into wild contexts to better understand consistent interindividual differences in parrots’ natural behaviors. More efforts should be directed towards methodological and conceptual standardization, in addition to applying temporal consistency analyses. Some additional gaps that have not been studied yet include research on the genetic basis, as well as morphophysiological and neuroendocrine mechanisms underlying temperament in Psittaciformes.
Keywords: Behavior; Individual differences; Parrots; Personality; Psittaciformes